The role of mesenchymal stem cell transplantation for ischemic stroke and recent research developments - Zhou, Li; Wang, Jiani; Huang, Jiagui; Song, Xiaosong; Wu, Youlin; Chen, Xia; Tan, Yongjun; Yang, Qin (Frontiers in Neurology, 2022)
Ischemic stroke is a common cerebrovascular disease that seriously affects human health. However, most patients benefit less from the current clinical treatment and do not engage in self-care. Stem cell transplantation is an emerging treatment and has been studied in various central nervous system diseases. More importantly, animal studies show that transplantation of mesenchymal stem cells (MSCs) can alleviate neurological deficits and bring hope for ischemic stroke treatment. This article reviews the biological characteristics of MSCs and discusses the mechanism and progression of MSC transplantation, to provide new therapeutic directions for ischemic stroke.